Single molecule spectroscopic studies of acid-base bifunctional thin-film catalysts - Usman, Abdulhafiz Onimisi (Kansas State University, 2022)
This dissertation describes the use of single molecule spectroscopy to study the distribution of active sites on silica-supported cesium catalysts and amine-functionalized silica films with acid-base gradients. These catalysts are important for the common C-C coupling aldol condensation reactions. This work also demonstrates the use of single molecule (SM) methods to study the relationship between the distribution of acidity on catalytic surfaces and chemical reactivity. In the first project, a dual-color ratiometric SM method was used to study the acidity distributions on Mg-Zr-Cs/SiO₂ catalyst films with different cesium loading using C-SNARF-1 as a pH-sensitive probe. The dye was found to be an effective indicator of local activity between pH 3 and pH 6.2. Single molecule emission data were collected from the catalyst films as a function of cesium content for films ranging from 0 to 20% cesium. The histograms of the emission ratios obtained for each film revealed a broad distribution of acidic properties particularly on films with high cesium loading. In the second project, a gradient silica film incorporating an amine gradient was synthesized. The formation and composition of the amine gradients were verified using spectroscopic ellipsometry, water contact angle, and XPS measurements. SM methods were used to probe the local acidity distribution on these gradients. Nile Red, typically used as a solvatochromic probe, was used to detect changes in the acid-base properties of the films. The single molecule data revealed a broad bimodal distribution of Nile Red spectra that varied along the gradient. This study provided data relevant to the use of aminosilane-modified silica catalysts in bifunctional cooperative chemical catalysis. In the final project, the SM study of the aldol condensation of Nile Red dye incorporating an aldehyde moiety with silica-bound acetophenone was introduced. The reactions were carried out on different sections of a bifunctional gradient film and the preliminary results show a link between activity distribution and chemical reactivity.
Keywords: Single-molecule characterization fluorescence spectroscopy